Synthesis of New Chitosan from an Endemic Chilean Crayfish Exoskeleton (Parastacus Pugnax): Physicochemical and Biological Properties - Palacios-Pino, J (Multidisciplinary Digital Publishing Institute (MDPI), 2021)
Chitin is one of the most abundant natural polysaccharides in the world and it is mainly used to produce chitosan by a deacetylation process. In the present study, the extraction of chitin and chitosan from the Parastacus pugnax (P. pugnax) crayfish exoskeleton was studied for the first time. Thus, the P. pugnax crayfish exoskeleton was converted to chitosan following the steps of depigmentation, deproteinization, and deacetylation. The produced chitosan (Chitosan-CGNA) was characterized in terms of the protein content, solubility, degree of deacetylation, viscosity, molecular weight, FTIR, SEM, XRD, antimicrobial, and antioxidant activity. The results showed that the obtained chitosan had a high degree of deacetylation (91.55%) and a medium molecular weight (589.43 kDa). The antibacterial activity of the chitosan was tested against bacterial strains relevant for the food industry and the lowest minimum inhibitory concentration (MIC) values were evidenced with Salmonella tiphymurium (S. typhimurium), Staphylococcus aureus (S. aureus), Enterococcus faecalis (E. faecalis) and Listeria. Monocytogenes (L. monocytogenes). Moreover, the Chitosan-CGNA showed an effect on DPPH radical scavenging activity, and its antioxidant activity was dependent on concentration and deacetylation degree. These results suggest that P. pugnax exoskeleton could be an excellent natural source for the production of chitosan with potential applications in the health system, and to prevent infections associated with pathogens strains. © 2021 by the authors. Licensee MDPI, Basel, Switzerland.